Ultra-High Performance Liquid Chromatography (UHPLC) untuk Kuantifikasi Gabapentin dalam Granul dan Kapsul - rahmayati rusnedy (JURNAL FARMASI DAN MAKANAN, 2022)
Ultra-High Performance Liquid Chromatography (UHPLC) has become the modern standard HPLC platform in recent years. UHPLC as an ideal separation tool for the analysis of complex mixtures with a shorter analysis time is very suitable to be used as a fast and precise method. This study aims to determine the quantitative determination of gabapentin in the form of intermediate products, namely granules and finished products, namely capsules from 1 production batch using the UHPLC method. The results of the quantitative examination of the average content (% recovery) of gabapentin in granule and capsule samples quantified by the UHPLC method met the compendial requirements and internal specifications compared to the standard gabapentin recovery values. The % recovery obtained is 98.254% for gabapentin granules and 97.784% for gabapentin capsules, which means it is still in the 95%-105% range. While the %RSD value is 0.735 for granules and 0.839 for capsules, which means it has an RSD value of <2%. % precision of gabapentin granules was 99.558% with %RSD 0.407, and % intermediate precision gabapentin capsules was obtained 98.845% with %RSD 0.678. In conclusion, based on the quantitative results obtained meet the expected specifications, so it can be considered for use for routine analysis and quality control of medicinal ingredients, in the inspection of intermediate products and other finished drug products in the pharmaceutical industry quickly and accurately.